Notes sur l’historiographie des loisirs - Emmanuel Roudaut (Revue Française de Civilisation Britannique)
After a period of considerable expansion in the 1960s and 1970s, the historiography of leisure pursuits has given rise to contrasting, often pessimistic, assessments. New questions have superseded the initial influence of figures such as E.P. Thompson and Eric Hobsbawm, manifest in the interest shown in the “poor man’s leisure pursuits”, as well as in the concern to link the study of popular culture with that of social antagonisms. At p0resent, the Industrial Revolution and its presumed destructive impact on popular culture occupy a less central place in works more concerned with bringing to the fore elements of continuity; this is conveyed by a greater diversity in the periods under study. Increased attention is paid to questions of gender, age and membership of a local community, which is at times detrimental to the notion of social class. Some see in this a more detailed perspective, better able to account for complex phenomena, whereas others fear that it marks a drift which would tend to neglect the relations of economic and political domination, prevalent in the area of leisure activities as elsewhere.